Pengaruh Literasi Keuangan dan Akses Keuangan Terhadap Perkembangan Usaha Mikro Kecil Menengah di Yogyakarta - Roma Nanda Aprina Pardede; Zaenal Wafa (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Especially in Indonesia, MSMEs play a significant role in economic development and growth and are the largest economic actors in the country. This research aims to study how financial literacy and financial access impact the development of micro, small, and medium enterprises (MSMEs) in Yogyakarta. In addition, this research measures financial literacy and financial access for MSMEs in Yogyakarta. Owners and managers of small and medium enterprises (MSMEs), Pecel Lele Pak Sony and Warmindo Sinar Bahagia in Yogyakarta, are the samples for this research. Using qualitative methods, this research collects data through interview techniques. The level of influence of financial literacy and financial access on the growth of MSMEs in Yogyakarta is still low.